2021
DOI: 10.48550/arxiv.2103.08339
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barrow HDE model for Statefinder diagnostic in non-flat FRW universe

Abstract: In this work we study a non-flat Friedmann-Robertson-Walker universe filled with a pressure-less dark matter (DM) and Barrow holographic dark energy (BHDE) whose IR cutoff is the apparent horizon. Among various DE models, (BHDE) model shows the dynamical enthusiasm to discuss the universe's transition phase. According to the new research, the universe transitioned smoothly from a decelerated to an accelerated period of expansion in the recent past. We exhibit that the development of q relies upon the type of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, if one desires to extend holographic dark energy in a non-flat universe, the above length should be suitably extended [79,80]. Hence, in the case of Barrow holographic dark energy this recipe should be followed too (note that in [81] it was tried to apply Barrow holographic dark energy in a non-flat universe but with L being the Hubble horizon, a choice that is known to be not correct [8,82] since it cannot lead to acceleration). Since the corresponding extension is slightly different for closed and open cases, in the following subsections we examine them separately.…”
Section: Barrow Holographic Dark Energy In Non-flat Geometrymentioning
confidence: 99%
“…However, if one desires to extend holographic dark energy in a non-flat universe, the above length should be suitably extended [79,80]. Hence, in the case of Barrow holographic dark energy this recipe should be followed too (note that in [81] it was tried to apply Barrow holographic dark energy in a non-flat universe but with L being the Hubble horizon, a choice that is known to be not correct [8,82] since it cannot lead to acceleration). Since the corresponding extension is slightly different for closed and open cases, in the following subsections we examine them separately.…”
Section: Barrow Holographic Dark Energy In Non-flat Geometrymentioning
confidence: 99%
“…A number of works explored the interacting Ricci holographic dark energy models (Chimento et al 2013a(Chimento et al , 2013bChimento & Richarte 2013, 2012. The recently proposed Barrow entropy formula (Barrow 2020) has led to formulation of the Barrow holographic dark energy model (Saridakis 2020) which has found many applications in cosmology (Saridakis 2020;Dixit et al 2021;Setare 2006;Huang & Li 2004;Chakraborty et al 2021;Bhardwaj et al 2021;Srivastava & Sharma 2021;Sheykhi 2021;Abreu et al 2020;Pradhan et al 2021;Sharma et al 2021;shikha, Adhikary et al 2021;Al Mamon et al 2020). Pandey (2017) showed that growth of structure in the universe starting from its initial smooth state leads to dissipation of configuration entropy.…”
Section: Introductionmentioning
confidence: 99%
“…The area law entropy expression is restored by choosing ∆ = 0 which accordingly corresponds to the simplest horizon structure, while ∆ = 1 expresses the most intricate surface structure. There are some investigations on Barrow entropy in the cosmological and gravitational setups [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Introductionmentioning
confidence: 99%